Asociaciones de Diatomeas en Paleoambientes Cuaternarios de la Costa Sur de la Provincia de Buenos Aires, Argentina - GUTIÉRREZ, BEATRIZ TÉLLEZ; SCHILLIZZI, ROBERTO (Pesquisas em Geociências, 2002)
<!-- .p { text-align: justify; } --> Sedimentary platforms of the south coast of Buenos Aires province (Argentine) were analised. A palaeoenvironmental evolution is established based on geological surveys, diatoms and sediment analyses. The information may be summarized in three stages: 1) during Pleistocene, ca.16.000 and 12.000 years B.P., lacustrine deposits, with eolic influence were identified; 2) between 8.000 and 6.500 years B.P. movile dunes morphology is associated with moments of climatic changes and increase in water supply to the area, favouring the establishment of shallow bodies colonized by fresh to brackish water assemblages of diatoms with litoral and acuatic macroflora development. There is a continentalization of the lagoons to the end of this stage; 3) ca. 5.300 and 4.800 years B.P., the oriental edge of the platform records marine conditions.